Sustainable Development of the Arctic Indigenous Communities: The Approach to Projects Optimization of Mining Company - Andrey Novoselov; Ivan Potravny; Irina Novoselova; Violetta Gassiy (Sustainability, 2020)
The article discusses the issues of sustainable development of indigenous communities in the Arctic based on the optimization of projects of mining companies. The purpose of the article is to develop tools for decision-making to optimize the mining projects based on economic and mathematical models. The authors suppose that, by comparing and selecting different options for resource extraction, the use of various technologies and the impact of projects, the conditions of the traditional life of indigenous peoples, the preservation of health, it is possible to find a compromise solution for stakeholders. The case-study of Alrosa—a diamond giant mining in Yakutia is researched in the paper. To ensure sustainable development of traditional lands, it is proposed to optimize mining projects, in order to carry out a project maneuver during Arctic development. The project maneuver of the mining company makes it possible to choose the optimal solution from the existing alternatives for the extraction of minerals. The authors propose criteria and procedures for the selection of alternative options for the implementation of extractive projects. The alternative projects selected in this way make it possible to compensate to indigenous communities for the negative impact during industrial development of the Arctic.